Neural Network Modelling of Energy Systems - Kalogirou, Soteris A. (My University, 2004)
Artificial neural networks, or simply neural networks, are collections of small, individual interconnected processing units. Information is passed between these units along interconnections. An incoming connection has two values associated with it, an input value and a weight. The output of the unit is a function of the summed value. Neural networks, although implemented on computers, are not programmed to perform specific tasks. Instead, they are trained with respect to past history data sets until they learn the patterns presented to them. Once they are trained, new unknown patterns may be presented to them for prediction or classification.
Keywords: Artificial neural networks; Energy system